A biomechanical analysis of barefoot versus shod distance running - Picha, K. J.; Weber, M. L.; Welch, C. E. (International Journal of Athletic Therapy & Training, 2014)
The article presents an analysis of studies conducted to investigate biomechanical differences between barefoot and shod distance running. Topics discussed include selection of studies from various online resources such as Embase through January 2013, comparison of barefoot and shod conditions, and dependent variables used include ground reaction forces. The analysis suggests more research is needed for better understanding of the biomechanical effects of barefoot running.